Pengaruh likuiditas dan leverage terhadap agresivitas pajak - Endin Alfin, Muhammad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The phenomenon of tax aggressiveness regarding companies operating in the health services sector is affiliated with companies in Singapore, namely PT RNI which has been registered as a limited liability company but in terms of capital, the company relies on affiliate debt for a living. This means that owners in Singapore provide loans to RNI in Indonesia. Because its capital is included as tax-deductible debt, RNI avoids liability. The financial statements recorded a loss so that no taxes went into the state. RNI 2014 financial report, recorded debt of Rp 20.4 billion with a company turnover of Rp 2.178 billion. There was a retained loss in the same year's report amounting to Rp. 26.12 billion. Based on the financial statements, this is no longer logical, so the Special DJP Regional Office conducts an examination. Another method used by PT RNI is to utilize Government Regulation 46/2013 on Income Tax specifically for MSMEs, with a final income tax rate of 1 percent. This study aims to obtain empirical evidence of the effect of liquidity and leverage on tax aggressiveness. The objects used are 11 companies in various industrial sectors listed on the Indonesia Stock Exchange in 2016 – 2020 which were selected by purposive sampling. The analysis technique for this research uses multiple linear regression analysis. Based on data analysis, it was found that liquidity had no statistically significant effect on tax aggressiveness and leverage had no statistically significant effect on tax aggressiveness.